2010
DOI: 10.4049/jimmunol.0902515
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Stromal Lymphopoietin Receptor-Mediated IL-6 and CC/CXC Chemokines Expression in Human Airway Smooth Muscle Cells: Role of MAPKs (ERK1/2, p38, and JNK) and STAT3 Pathways

Abstract: Thymic stromal lymphopoietin (TSLP) plays a pivotal role in allergic diseases such as asthma, chronic obstructive pulmonary disease, and atopic dermatitis. Enhanced TSLP expression has been detected in asthmatic airways that correlated with both the expression of Th2-attracting chemokines and with disease severity. Although cumulative evidence suggests that human airway smooth muscle (HASM) cells can initiate or perpetuate the airway inflammation by secreting a variety of inflammatory cell products such as cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 59 publications
7
96
0
Order By: Relevance
“…More recently, three groups showed that two members of the Janus family kinases, Jak1 and Jak2 are activated in TSLP signaling (29 -31). Erk1/2, JNK1/2, and p38 have also been reported as intermediates in TSLP signaling (29,32). In agreement with these reports, our proteomic data indicates that Jak2, Erk1/2, JNK1/2, and p38 were all indeed inducibly phosphorylated by TSLP stimulation.…”
Section: Btk Protein Tyrosine Kinasesupporting
confidence: 91%
See 1 more Smart Citation
“…More recently, three groups showed that two members of the Janus family kinases, Jak1 and Jak2 are activated in TSLP signaling (29 -31). Erk1/2, JNK1/2, and p38 have also been reported as intermediates in TSLP signaling (29,32). In agreement with these reports, our proteomic data indicates that Jak2, Erk1/2, JNK1/2, and p38 were all indeed inducibly phosphorylated by TSLP stimulation.…”
Section: Btk Protein Tyrosine Kinasesupporting
confidence: 91%
“…TSLP requires JAK1 and JAK2 to activate STAT5 (31). TSLP is also known to increase the phosphorylation of ERK1/2, JNK1/2, AKT, ribosomal protein S6, and 4E-BP1 (12,29,32,33). However, the knowledge of TSLP signaling obtained from biochemical experiments is scattered and the detailed signal transduction pathways responsible for various biological effects of TSLP still remain elusive.…”
Section: Thymic Stromal Lymphopoietin (Tslp)mentioning
confidence: 99%
“…3b and c) contain STAT3 and EGFR, among others. STAT3 has been shown to be involved as a transcriptional mechanism for thymic stromal lymphopoietin to induce a proinflammatory gene expression in ASM cells [30], whereas blocking EGFR may lead to a reduction in mucus hypersecretion [31]. Taken together, these results indicate that the regulation of biological processes in the airways is evidently different in asthma compared to controls.…”
Section: Discussionmentioning
confidence: 94%
“…TSLP induces IL-6 expression and is linked to asthma, chronic obstructive pulmonary disease, and atopic dermatitis [64]. IL-6 promotes a chronic inflammatory response by stimulating T-cells and B-cells [65].…”
Section: Inflammation and Cytokinesmentioning
confidence: 99%